Analisis Kompratif Sistem Mutu dan Sistem Manajemen Mutu Pada Kantor Akuntan Publik: Kajian Literatur Review - Nhamyra Imania Nabilla; Nazwa Syahira Triananda; Trinandari Prasetya Nugrahanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This article discusses the strategic role of quality system implementation in improving audit quality at Public Accounting Firms (KAP), specifically through the integration of Quality Control Standards (QMS) and Quality Management Systems (QMS). The main objective of this study is to analyze the relationship and influence between SPM and SMM on audit quality and explore the theoretical relevance through the Agency Theory approach. This research uses a literature study method by reviewing 19 scientific articles, consisting of 11 SINTA indexed national journals (at least SINTA 4) and 8 international journals published in the period 2015-2025. The results of the study show that integration between SPM and SMM can improve accountability, efficiency, and credibility of audit results, especially when supported by strong leadership, continuous supervision, and the use of modern audit technology. Consistent and adaptive implementation of quality systems is proven to increase client satisfaction and strengthen the auditor's position in facing the challenges of information asymmetry between principal and agent. Therefore, KAP is advised to make quality system development a strategic priority that is responsive to regulatory dynamics and industry demands.